Pelatihan dan Edukasi Berbasis Digital dalam Mewujudkan Budaya Keselamatan di Perguruan Tinggi - Raharjo, Agung; Suparni, Suparni; Ariyanto, Januar; Jannah, Farahul (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance new students' knowledge and skills regarding safety, health, and the campus environment through the development of digital modules uploaded to the Learning Management System (LMS). The methodology employs a model designed using the ADDIE instructional design approach to ensure effectiveness and participant engagement. This module was accessed by 22 new students at Universitas Pembangunan Nasional â€œVeteranâ€ Jakarta who completed the training online. A questionnaire was used as the data collection instrument to assess students' experiences, and the data were analyzed descriptively to evaluate the module's effectiveness in increasing safety awareness on campus. The results indicate that 77.3% of participants found the module easy to understand, and 68.2% were able to effectively identify campus safety facilities. Additionally, 63.6% of participants reported feeling more confident in handling emergency situations. These findings suggest that the digital module is not only relevant but also effective in enhancing the safety knowledge of new students. Therefore, further development of similar modules can significantly contribute to creating a safer and more sustainable campus environment.